A jovem mulher contemporânea urbana e os efeitos de sentido na discursividade da série televisiva Aline - Lima, Valquiria Botega de (2011)
This dissertation thematizes how the contemporary urban young woman constitutes herself discursively and signifies in the television series Aline, whose main character is a young woman who represents the complexity of the woman in contemporary universe, specifically in downtown of the largest city of Latin America, São Paulo. The central concern that drives this research is to understand how this subject is constituted and signifies itself and/or is signified in the discursive functioning of the verbal-visual materiality of the series in focus. To achieve this goal, we take into account the fact that the media-television product consists of an adaptation of a collection of books which brings Aline's comic strips and, by extension, the understanding of the identification/signification forms of the young woman in the series requires, firstly, an analytical study of the comic strips materiality. Moreover, we understand the media dissemination analysis of the series as necessary for allowing us to check the direction of meanings involving the character and the television program, due to Rede Globo`s interests: ensure the audience and the marketing of their product. Through theoretical and analytical perspective of French Discourse Analysis, in particular, Michel Pêcheux` studies, we based our work under a discursive look, in which concerns the concepts of discourse, subject, effect(s) of meaning; silencing and interdiscourse (discursive memory). We build our study on the reflections of history, sociology and philosophy to make a brief resume about the history of the women in our country, in order to approximate the reflections about the young woman nowadays. Methodologically, we operate with the search of most recurrent themes in the comic strips for further comparative discussion regarding the series. The predominance of the themes also operated as part of the analytical corpus. Thus, we investigated the subject-character Aline signifying herself and being constituted in relation to: a) their boyfriends b) his parents, and c) society. Finally, with regard to the strips, we found that the character produces discourses against mandatory normalities about sexual female behavior, about romantic relationship and about family relationship. Besides that, the sexual issue is what potentiates protagonist`s speech. Regarding the series disclosure, we realize that the meanings that have circulated about this media product and about the young woman (Aline) are affiliated to the ideological and discursive formation of consensus, since they mean contrary to the questioning, and aimed to drive the meanings about the young women from discourses that have already been worked and accepted in social and media space. A discursive analysis of the series allows us to observe and conclude that the subject-character Aline, in spite of retaining some features from the character-source (comic strips), it moves away, especially when the issue of sex slides to the issue of love and happiness. In our description and interpretation gesture regarding the romantic, family and social relationships, we realize that Aline signifies and constitutes herself in a complex and contradictory relationship that combines the linkages between traditional and nontraditional, the private life (domestic space and its functions) and the public life (urban social space), the old and the new structure of romantic relationship; naturalness (consensus) and conflict (disagreements).